Developing Android Game-Based Learning Media “Go Accounting” in Accounting Learning - Agatha Saputri; Sukirno Sukirno; Heri Kurniawan; Taufik Probowasito (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
This study aims to: (1) develop android game-based learning media “Go Accounting” in trading company accounting learning (2) reveal the feasibility of the develop learning media according to material experts, media experts, teachers, and student. This study is research and development that refers to the ADDIE model. The subjects of the trial are the students of class XI accounting of vocational high school. The data collection is done through interviews and questionnaire. The instruments used are interview guide, expert validation questionnaire, teacher response questionnaire, and student response questionnaire. The feasibility of the develop learning media is analyzed using the quantitative 5 category conversion. The result of this study is Android game-based learning media “Go Accounting”. The development of learning media is feasible according to material experts, media experts, teachers, and students each of whom subsequently gave a score of 4.18, 4.35, 4.70, and 4.22.